Pengaruh Kecemasan Terhadap Konsentrasi Pada Atlet Renang Petrokimia Gresik - Bella Pratama (Journal of Sport Science and Education, 2019)
This study aims to determine whether there is an influence between anxiety with concentration in swimming athletes Petrokimia, Gresik. Hypothesis of work (Ha) proposed is There is an influence between anxiety with concentration in swimming athletes Petrokimia, Gresik. Subjects in this study were 30 swimming athletes. Data were collected using questionnaires in the form of anxiety scale and grid concentration scale. Data analysis technique using product moment correlation. The result of data analysis shows the correlation coefficient value of 0.132 with the significance level of 0.000 (p <0,005). These results indicate that there is a significant influence between anxiety with concentration on swimming athletes Petrokimia, Gresik, and positive values indicate a unidirectional relationship between two variables of anxiety and concentration. the higher the anxiety level of the athlete the lower the concentration that the athletes have, and vice versa.